2021
DOI: 10.1021/acs.jpcc.1c02323
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Robust Half-Metallicity in Strained Manganite Films

Abstract: We investigated the relationship between ferromagnetism and metallicity in strained La 0.67 Ca 0.33 MnO 3 films grown on lattice-mismatched NdGaO 3 (001) by means of spectroscopic techniques directly sensitive to the ferromagnetic state, to the band structure, and to the chemical state of the atoms. In this system, the ferromagnetic metallic (FMM) phase spatially coexists with an insulating one in most of the phase diagram. First, the observation of an almost 100% spin polarization of the photoelectrons at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…At 1.5 GPa, the reduced ε b fails to stabilize an AFI state. The monoclinic AFI phase partially melts into the orthorhombic FMM phase, and accommodation strain forms at their interfaces, which could involve the formation of spatially inhomogeneous PS states. , As shown in Figure b, at 3.2 GPa, the FMM phase dominates, but a small volume fraction of AFI remains, which is similar to that of LCMO/KTO at 2.6 GPa (see Figure S11). Based on an estimated pressure dependence of strain, compressive stress induced by 3.2 GPa is calculated to be about 1%.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…At 1.5 GPa, the reduced ε b fails to stabilize an AFI state. The monoclinic AFI phase partially melts into the orthorhombic FMM phase, and accommodation strain forms at their interfaces, which could involve the formation of spatially inhomogeneous PS states. , As shown in Figure b, at 3.2 GPa, the FMM phase dominates, but a small volume fraction of AFI remains, which is similar to that of LCMO/KTO at 2.6 GPa (see Figure S11). Based on an estimated pressure dependence of strain, compressive stress induced by 3.2 GPa is calculated to be about 1%.…”
mentioning
confidence: 86%
“…Different symmetries of epitaxial strain can also induce quite dissimilar octahedral distortions, orbital orderings, and structural/magnetic domain morphologies. In general, epitaxial strains can anisotropically change the atomic spacing along the in-plane and out-of-plane directions, and on the contrary, hydrostatic pressure compresses the lattice isotropically. Therefore, the hydrostatic pressure and epitaxial strain could be considered as complementary tuning knobs. Manganite films have attracted much attention, arising from their colossal magnetoresistance, phase separation (PS), charge/orbital/spin ordering, and half-metal feature. ,, However, utilizing hydrostatic pressure and epitaxial strain cooperatively to engineer the structural/octahedral distortions of manganite thin films has rarely been addressed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Transition metal oxides are widely studied due to their broad range of versatile functionalities arising from the complex interplay between charge, orbital, spin, and lattice degrees of freedom. [ 1–6 ] In this family, it was shown that some composition present two antagonist properties at the same time: high electrical conductivity and visible‐range optical transparency. This class of materials is called transparent conductive oxide (TCO).…”
Section: Introductionmentioning
confidence: 99%